ANALISIS EFEKTIVITAS MODAL KERJA DALAM MENINGKATKAN LIKUIDITAS DAN PROFITABILITAS PADA PT. SYUHADA BERSAUDARA KABUPATEN ROKAN HULU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine and analyze the effectiveness of working capital in improving liquidity and profitability in PT. Syuhada Bersaudara Kabupaten Rokan Hulu. In this study using quantitative descriptive data types, the data sources used are primary data obtained through interviews, and secondary data using financial statement data of PT. Syuhada Bersaudara Kabupaten Rokan Hulu for the 2016-2020 period and other data related to research material, and using ratio analysis.            The results of this study are as follows: First, the effectiveness of working capital on the liquidity ratio with indicators of the current ratio and cash ratio is in the good category although there is a decrease and increase in value in each period. Second, the effectiveness of working capital on profitability ratios with indicators of net profit margin, return on investment and return on equity are in the poor category. The low value of profitability ratios in NPM, ROI and ROE was caused by an increase in total assets and high expenses, while product sales experienced fluctuating developments. Keywords : Working Capital, Liquidity and Profitability